Cultura organizacional e mudança cultural: a contribuição sahliniana e o caso Cedejor - Mascarenhas, André Ofenhejm (2006)
This thesis proposes new directions within the discussions of organizational culture. Traditionally, the debates on the theme in the field of organization theory incorporate anthropological frameworks, in special, the premises and ideas which compose the functionalist and interpretative paradigms. Within this interdisciplinary appropriation, the discussions on cultural change in organizations did not assimilate frameworks which allowed the analysis of the ways social groups actually change and evolve. In fact, the disciplinary matrix of anthropology is characterized by the opposition of diachrony and synchrony - which assumes the format of opposing pairs such as system and event, history and structure, stability and change. Based on this opposition, anthropologists built theoretical traditions which highlight continuity in detriment of change, or structure in detriment of history. More recently, however, the ideas of Sahlins, or the structural, historical anthropology, suggest the inadequacy of the history-structure polarization as we recognize the complexity and specificity of the cultural phenomenon. Based on a theoretical proposal that suggests the inseparability of continuity and change, Sahlins proposes important redefinitions in the classical concepts of culture. These redefinitions would allow the incorporation of a serious of issues historically neglected by the classical anthropological paradigms; in special, cultural change. This thesis suggests that the assimilation of Sahlinsí proposals to the discussions of organizational culture has the potential of advancing the debates on the ways organizations evolve as it allows the analysis of the continuities and discontinuities which characterize these cultural systems. As it questions the traditional concepts of organizational culture, this movement would contribute to the refinement of the cultural debates within organization theory, e.g., allowing the development of a cultural perspective to organizational learning. The potential contribution of Sahlinsí proposals is illustrated by an ethnographic case study held in CEDEJOR Albard„o, an NGO which aggregates 30 teenagers from the seventh rural district of Rio Pardo, Rio Grande do Sul, Brazil. CEDEJOR´s goals include promoting entrepreneurship, the personal development of the rural youth and the sustainable development of their communities through participative educational processes. Based on the ideas of Sahlins, the analysis of the case study suggests that culture is system and event, ambiguity and consensus, and structure and history simultaneously.